2017
DOI: 10.1088/1361-665x/26/3/037003
|View full text |Cite
|
Sign up to set email alerts
|

On the effect of polarization direction on the converse magnetoelectric response of multiferroic composite rings

Abstract: The application domain of composite multiferroic materials with magnetoelectric coupling has been widening on the nano-, micro- and macro-scales. Generally, a composite multiferroic material consists of two, or more, layers of a piezoelectric material and a magnetostrictive material. In turn, the proliferation of multiferroics in more applications is accompanied by a keen focus on understanding the effect of material phases, geometry, bonding interface and arrangement of phases by performing theoretical, numer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 67 publications
(87 reference statements)
2
18
0
Order By: Relevance
“…Finally, the vibrational displacements were induced by subjecting the piezoelectric cylinder to a radial AC electric field (30 kHz) using a waveform generator (Agilent 33210A) and a high voltage amplifier (Trek PZD700A) at a level of 20 kV/m. The selection of the amplitude and frequency of the electric field was based on previous studies reported in Newacheck et al (2018), Chavez et al (2016) and Youssef et al (2017a).…”
Section: Experimental Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the vibrational displacements were induced by subjecting the piezoelectric cylinder to a radial AC electric field (30 kHz) using a waveform generator (Agilent 33210A) and a high voltage amplifier (Trek PZD700A) at a level of 20 kV/m. The selection of the amplitude and frequency of the electric field was based on previous studies reported in Newacheck et al (2018), Chavez et al (2016) and Youssef et al (2017a).…”
Section: Experimental Approachmentioning
confidence: 99%
“…Specifically, we have experimentally investigated the effect of the bias magnetic field direction, electric field direction, and bonding methods, while analytically explored the effect of mechanical boundary conditions, and developed validated computational models (Newacheck et al 2018;Chavez et al 2016;Youssef et al 2020a, b). In the previous efforts, not only we investigated and reported the overall response, i.e., the converse magnetoelectric coefficient, but also, we thoroughly studied the behavior of each of the constituents such as the direction of polarization of the piezoelectric cylinder (Youssef et al 2017a) as well as the magnetostriction response of Terfenol-D (Youssef et al 2017b). In regards to the latter, Youssef et al (2017b) experimentally mapped the magnetoelastic response of the Terfenol-D cylinder in response to a DC magnetic field to elucidate the interrelation between the changes in magnetization and applied bias magnetic field.…”
mentioning
confidence: 99%
“…Despite the challenges in fabrication and characterization of geometries, such as concentric cylinder structures with varying interface conditions, prior experimental research documented the effect of materials and stacking on the strain-mediated magnetoelectric coefficient. For example, our group recently investigated the interrelation between the interface conditions and the magnetoelectric coefficient of composite PZT/ Terfenol-D bilayer cylinders (Chavez et al, 2016;Youssef, 2017a;Youssef, 2017b). In addition, tri-layer concentric cylinder composite configurations of Ni/ PZT/Ni and FeCO 2 /PZT/Ni have been experimentally investigated by Yakubov et al and Ge et al, respectively (Ge et al, 2018;Yakubov et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…As a first demonstration of a fully integrated, thin‐film magnetoelectric device, these values can only be compared against existing bulk magnetoelectric counterparts. Nevertheless, the values produced here were found to compare favorably and even compete with some bulk magnetoelectrics, whose coefficients were often on the same order, such as 20 to 82.5 mG cm V −1 for a PZT/Terfenol‐D/PZT composite, or higher, such as 282 and 443 mG cm V −1 for a PZT/Terfenol‐D composite . While some thin magnetic films on bulk PZT substrates may yield larger coefficients ranging from 40 to 1650 mG cm V −1 or greater, we have no doubt that additional optimizations of the entirely thin‐film form of magnetoelectric composites can further increase their coupling coefficients and resulting tunability.…”
mentioning
confidence: 59%